Perancangan E-Government Sistem Administrasi Pada Stasiun Meteorologi Menerapkan User Center Design (UCD) - Santi Nuripani Sahroningsih Esa Putri; Lukman Bachtiar (Journal of Computer System and Informatics (JoSYC), 2020)
E-Government, namely the use of information and communication technology, for various purposes in order to implement effective and efficient government administration and operational activities in office activities. The first problem experienced includes the process of managing incoming mail data and outgoing mail data, which are still scheduled in the letter agenda book and important documents are still stored in the odner and are not managed by the system so that if there is a loss or computer error one day, all data will be lost and need more space and costs to manage documents. The second problem is that service activities in the form of requests for weather and climate data are still not integrated and without applications so that service users need less efficient time and energy because they do not know or lack the requirements to get the required climate weather information. Seeing the obstacles encountered. Therefore, the system that will be created by researchers is a web-based information system that functions as a data processing medium, both incoming and outgoing mail data and data on transaction letters requesting weather and climate data. By implementing this information system, it is hoped that it can minimize the errors and difficulties experienced so far and help employees to search and provide data in a fast, precise and without problems. In designing the E-Government application, the Administration System at the Meteorological Station uses the Waterfall method and uses the Yii Framework in making applications